Campylobacter jejuni infection of conventionally colonized mice lacking nucleotide-oligomerization-domain-2. Issue 1 (December 2017) - Bereswill, Stefan; Grundmann, Ursula; Alutis, Marie; Fischer, André; Heimesaat, Markus
Abstract Background The nucleotide-binding oligomerisaton protein 2 (NOD2) constitutes a pivotal sensor of bacterial muramyl dipeptide and assures expression of distinct antimicrobial peptides and mediators produced by enterocytes and immune cells directed against pathogens includingCampylobacter jejuni . We here elucidated the role of NOD2 during murineC. jejuni infection in more detail. Results Conventionally colonized NOD2 deficient (NOD2−/− ) mice and corresponding wildtype (WT) counterparts were perorally infected withC. jejuni strain 81–176 on three consecutive days. The pathogen colonized both WT and NOD2−/− mice only sporadically until day 14 post infection (p.i.). However, the slightly higher prevalence ofC. jejuni in NOD2−/− mice was accompanied by higher intestinalEscherichia coli loads known to facilitateC. jejuni colonization. Neither overt macroscopic (clinical) nor microscopic sequelae (such as colonic epithelial apoptosis) could be observed upon murineC. jejuni infection of either genotype. Innate immune responses were less distinctly induced inC. jejuni infected NOD2−/− versus WT mice as indicated by lower colonic numbers of neutrophils in the former. Conversely, adaptive immune cell counts including T lymphocytes were higher in large intestines of NOD2−/− as compared to WT mice that were paralleled by increased colonic IL-6 secretion and higher TNF and IL-18 mRNA expression levels in large intestines of the former. Only in NOD2−/− mice, however, colonic IL-22 mRNA expression was down-regulated at day 14 p.i. Whereas viable commensal intestinal bacteria could exclusively be detected in mesenteric lymph nodes and livers of NOD2−/− mice, bacterial translocation rates to kidneys and spleen were NOD2 independent. Notably, large intestinal mRNA expression levels of mucin-2, constituting a pivotal factor involved in epithelial barrier integrity, were comparable in naive andC. jejuni infected mice of either genotype. Conclusion NOD2 is involved in the well-balanced regulation of innate and adaptive pro-inflammatory immune responses of conventional mice uponC. jejuni infection.